Raman Shifts in Electron-Irradiated Monolayer MoS2 - Parkin, William M; Balan, Adrian; Liang, Liangbo; Das, Paul Masih; Lamparski, Michael; Naylor, Carl H; Rodríguez-Manzo, Julio A; Johnson, A. T. Charlie; Meunier, Vincent; Drndić, Marija (ACS nano, 2016)
We report how the presence of electron-beam-induced sulfur vacancies affects first-order Raman modes and correlate the effects with the evolution of the in situ transmission-electron microscopy two-terminal conductivity of monolayer MoS2 under electron irradiation. We observe a red-shift in the E′ Raman peak and a less pronounced blue-shift in the A′1 peak with increasing electron dose. Using energy-dispersive X-ray spectroscopy and selected-area electron diffraction, we show that irradiation causes partial removal of sulfur and correlate the dependence of the Raman peak shifts with S vacancy density (a few %). This allows us to quantitatively correlate the frequency shifts with vacancy concentration, as rationalized by first-principles density functional theory calculations. In situ device current measurements show an exponential decrease in channel current upon irradiation. Our analysis demonstrates that the observed frequency shifts are intrinsic properties of the defective systems and that Raman spectroscopy can be used as a quantitative diagnostic tool to characterize MoS2-based transport channels.